Fakes, lies, and forgeries : rare books and manuscripts from the Arthur and Janet Freeman Bibliotheca Fictiva Collection - Havens, Earle (Sheridan Libraries, Johns Hopkins University, 2016)
In addition to providing a checklist of 70 treasures from the Arthur and Janet Freeman Bibliotheca Fictiva Collection, this beautifully-illustrated volume includes five essays that explore the phenomenon of forgery as a creative literary form and provide an interesting and informative sense of the broader collection. With nearly 1,700 individual items, the Bibliotheca Fictiva Collection is the largest and most comprehensive collection of books and manuscripts of forgery in the world. Highlights include editions of Jesus' posthumous "Letter from Heaven," eyewitness accounts of the Fall of Troy, annotated books from Shakespeare's personal library, Alpine inscriptions recording Noah's settlement of Vienna after the Flood, and a first-hand account of the discovery of Homer's tomb. The collection was assembled over a 50-year period and acquired by the Sheridan Libraries of Johns Hopkins University in 2011. - Exhibition: Johns Hopkins Krieger School of Arts, Baltimore, USA (05.10.2014 - 01.02.2015)